1999
DOI: 10.1007/s004240051083
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-dependent, slowly activating K + current ( I Ks ) and its augmentation by carbachol in rat pancreatic acini

Abstract: Acetylcholine-stimulated exocrine secretion of Cl- and water requires the concomitant activation of K+ channels. However, there has not been much investigation of the carbachol- (CCH-) activated K+ channel of rodent pancreatic acini. Here, in a study of rat pancreatic acini, we characterize a voltage-dependent, slowly activating outward current (I(Ks)) that is augmented by CCH. Intact acini were obtained by enzymatic digestion and fast-whole-cell patch-clamp was applied. With symmetrical [Cl-] (32 mmol/l) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…K i values for K v 7.1/KCNE1, K v 7.1/KCNE2 and K v 7.1/KCNE3 were 3–10 μM, 0.4 μM, and 3–4 μM, respectively 68 , 70 , 82 , 86 , 87 . Voltage-gated K + currents in pancreatic acinar cells were shown to be inhibited by chromanol 293B with a K i value of 3 μM 72 . This result supports voltage-gated K + channels being composed of K v 7.1 and KCNE1 β-subunit in acinar cells.…”
Section: Kcnq1 (Kv71 Kvlqt1) and Kcne1 (Mink)mentioning
confidence: 94%
See 1 more Smart Citation
“…K i values for K v 7.1/KCNE1, K v 7.1/KCNE2 and K v 7.1/KCNE3 were 3–10 μM, 0.4 μM, and 3–4 μM, respectively 68 , 70 , 82 , 86 , 87 . Voltage-gated K + currents in pancreatic acinar cells were shown to be inhibited by chromanol 293B with a K i value of 3 μM 72 . This result supports voltage-gated K + channels being composed of K v 7.1 and KCNE1 β-subunit in acinar cells.…”
Section: Kcnq1 (Kv71 Kvlqt1) and Kcne1 (Mink)mentioning
confidence: 94%
“…Functional expression of the KCNQ1 gene has also been demonstrated in the kidney, stomach, small intestine, colon, 68 - 71 pancreatic acini, 69 , 72 , 73 and pancreatic ducts 13 . Immunoreactivity of the K v 7.1 protein was reported in the parietal cells of the stomach, in the basolateral membrane of small intestinal and colonic crypt cells, 69 , 74 , 75 and in acinar and duct cells of the pancreas 13 , 69 .…”
Section: Kcnq1 (Kv71 Kvlqt1) and Kcne1 (Mink)mentioning
confidence: 95%
“…In the heart, Kv7.1 associates with the ancillary subunit KCNE1 to constitute the channel responsible for the late repolarizing current termed I Ks (Barhanin et al, 1996;Sanguinetti et al, 1996). Kv7.1 also associates with KCNE1 in the inner ear, where they regulate auditory function and pancreatic acinar cells where activation of the Kv7.1-KCNE1 channel provides the driving force for Cl − secretion (Kim and Greger, 1999;Köttgen et al, 1999;Warth et al, 2002). In addition, Kv7.1 channels in the pancreatic ß-cells contribute to the regulation of insulin secretion, and loss of function mutations in the KCNQ1 gene leads to impaired ß-cell insulin secretion, which is associated with type 2 diabetes (Ullrich et al, 2005;Unoki et al, 2008;Yasuda et al, 2008;Yamagata et al, 2011;Liu et al, 2014;Torekov et al, 2014;Min Lee et al, 2017;Zhang et al, 2020).…”
Section: Kcnq-encoded Potassium Channelsmentioning
confidence: 99%
“…KCNQ1 (KVLQT1, Kv7.1) and KCNE1 (IsK, minK) have been found in abundance in pancreatic acinar cells ( Kottgen et al, 1999 ; Bleich and Warth, 2000 ; Demolombe et al, 2001 ; Warth and Barhanin, 2002 ; Warth et al, 2002 ; Hayashi et al, 2012 ). By using mouse models associated with electrophysiological studies, Warth et al (2002) showed that KCNQ1 was predominantly located at the basolateral membrane and its co-assemblage with KCNE1 leads to a voltage-dependent K + current that was increased by cholinergic stimulation and inhibited by the KCNQ1 blocker ( Kim and Greger, 1999 ; Kottgen et al, 1999 ; Warth et al, 2002 ). The fact that inhibition of KCNQ1 channels diminishes intestinal Cl - secretion, made the authors suggest its involvement in pancreatic electrolyte secretion process.…”
Section: Expression Localization and Role Of Ion Channels In Healthmentioning
confidence: 99%